Professional Competency of English Teachers and PJOK at SMP Cahaya Pengharapan Abadi Medan - Tasya Gabriella Sianturi; Melody Sitorus; Nur Sakinah; Novita Sari Kaban; Hernita Siagian (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
This study aims to determine the competence of teachers when teaching and knowing qualifications whether or not including professional teachers at SMP Cahaya Pengharapan Abadi Medan. This study uses a descriptive qualitative research method. Source of data in the form of primary data. Data collection techniques are observation, interviews and documentation. The subjects of the study were English teachers and PJOK. The results showed that the four basic teacher competencies, both pedagogic competence, social competence, professional competence and personal competence, which were already possessed by English teachers and PJOK teachers as research subjects were good, but there were several points in these competencies that were not possessed. The percentage of teacher competence that is owned is above 85%.